The Evolution of Disability Perspective Models and Their Impact on Inclusive Education - Rashikj Canevska, Olivera; Chichevska Jovanova, Natasha (Faculty of Philosophy, Skopje, Republic of N. Macedonia, 2025)
Examining the different disability perspective models provides insight to the conceptions and attitudes towards the disabled community. When we talk about the connection between disability persoective models and inclusive education, generically there seems connection. It is essential to understand the differences between the various models of disability, as well as their separate histories, in order to fully appreciate the concepts of exclusion and inclusion. The objective of the paper was to explore the ideas of models of disability and its connection to educational system for students with disabilities, or more precisely its connection to inclusive education. To explore the connection between models of dis ability and education system, different literatures were collected from search engines, reviewed and analyzed from the angle of disability perspective models. The literature resources were analyzed from the perspectives interlinking to the role of disability mod els to the inclusive education. This paper analyzes the four main disability perspective models – the medical, social, biopsychosocial, and human rights models – and their application in inclusive education. It is explored that there seems strong connection of given disability models to inclusive education. The conclusion of the paper is that no single model fully addresses the complex needs of students with disabilities. Understanding the nuances of these models and their effects on special needs students is crucial for policymakers, educators, and stakeholders in the field of education.
Еволуцијата на моделите на гледишта за попреченоста и нивното влијание врз инклузивното образование
Keywords: Inclusive education, disability, medical model, social model, biopsychosocial model, human rights model, inclusion, rights of people with disabilities